Parent Firm Performance across International Joint Venture Life-cycle Stages - Reuer, Jeffrey J. (Journal of International Business Studies, 2000)
The benefits that firms obtain from investing in international joint ventures (IJVs) can be reinforced or reduced by the management of later stages of collaboration. This paper presents an analysis of the shareholder wealth effects of IJV formation and five types of IJV termination. The empirical findings challenge common assumptions in the IJV literature, contrast prior evidence on the performance implications of market entry and exit through acquisitions and divestitures, and demonstrate the value of integrating IJV life-cycle stages in future research.